Africa’s wars on women - Matthews, Ron; Mercy, Asiimwe (Taylor & Francis, 2026)
The world is becoming more violent. Currently, there are more than fifty ongoing armed conflicts, from Ukraine to Sudan, from Gaza to Afghanistan; indeed, the highest since World War II. Africa remains the region with the most state-based conflicts, numbering twenty-eight in 2023, nearly double the fifteen conflicts in 2013. Over the past thirty years, more than three-quarters of all African countries have been involved in armed conflict.Footnote3 Uniquely, Africa also suffers from what might be called repetitive conflicts, occurring repeatedly in the same countries, perpetuating divisions and entrenching hatred. Indeed, every civil war in Africa and the Middle East since 2003 (except for Libya) has been a continuation of a previous civil war. For example, Liberia and Somalia have each suffered two wars, Sudan three, and the Democratic Republic of Congo (DRC) an incomprehensible five in about a generation.
Keywords: International Relations; 4408 Political science